Cumulative nature of the health system’s performance and applied models of its organization - Smailov, B.T.; Andarova, R.K.; Vechkinzova, Ye.A. (BUKETOV BUSINESS REVIEW, 2021)
Objective: To structure the typology of applied healthcare system organization models and identify the dominants of their organizational mechanism and the parameters of their cumulative effectiveness at both micro and macro levels based on the review of existing approaches and the elaboration of theoretical constructs for analyzing the healthcare system’s performance. Methods: We used a wide range of system, structural, and comparative analysis methods. Results: We have reviewed the main range of studies on the cumulative performance of the health system as an integral indicator of its medical, social, and economic efficiency; justified the structure of medical services as a private, public, mixed public good; studied the typology of a modern health sector based on detailing the theoretical constructs underlying the applied models with the emphasis on the dominant organizational mechanism and the specifics of cumulative performance at both micro and macro levels. Conclusions: All applied models of the health system organization seek to find optimal performance. Comparative basis of the said models is the cumulative nature of their performance (medical, social, and economic) both at micro level and in macro dimension. Microeconomic medical efficiency generates organizational effectiveness of medical measures; social performance generates the degree of accessibility to medical services; and economic efficiency of healthcare generates resource productivity. At the macro level medical efficiency leads to innovation performance, social performance is manifested in the maximization of social utility, economic efficiency in the quality of life and human capital growth.